2005
DOI: 10.1103/physrevd.71.124009
|View full text |Cite
|
Sign up to set email alerts
|

Ringing wormholes

Abstract: We investigate the response of the traversable wormholes to the external perturbations through finding their characteristic frequencies and time-domain profiles. The considered solution describes traversable wormholes between the branes in the two brane Randall-Sundrum model and was previously found within Einstein gravity with a conformally coupled scalar field. The evolution of perturbations of a wormhole is similar to that of a black hole and represents damped oscillations (ringing) at intermediately late t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
225
1
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 156 publications
(237 citation statements)
references
References 50 publications
9
225
1
2
Order By: Relevance
“…The metric is exactly the same as the extremal Reissner-Nordström metric and the horizon is located at r = M . Classical stability of the Bocharova-Bronnikov-Melnikov-Bekenstein (BBMB) solution against the monopole perturbation has been addressed in [16][17][18]. For φ 2 > 6M…”
Section: Bocharova-bronnikov-melnikov-bekenstein Solutionmentioning
confidence: 99%
“…The metric is exactly the same as the extremal Reissner-Nordström metric and the horizon is located at r = M . Classical stability of the Bocharova-Bronnikov-Melnikov-Bekenstein (BBMB) solution against the monopole perturbation has been addressed in [16][17][18]. For φ 2 > 6M…”
Section: Bocharova-bronnikov-melnikov-bekenstein Solutionmentioning
confidence: 99%
“…Among important processes, the proper oscillations of higher dimensional black holes as a response to an external perturbations have been actively studied recently [3]- [16]. These oscillations are governed by the so-called quasinormal modes, which have been in the focus of gravitational research during recent years because of a few reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, perturbations of more exotic objects such as wormholes, white holes, or naked singularities have been investigated. It was found that the quasinormal spectrum of Schwarzschild black holes differs from wormholes 118 and white holes 119 . Therefore, these objects, if they exist, might be detected through observations of their quasinormal ringing.…”
Section: Quasinormal Modes Of D = 4 Black Holesmentioning
confidence: 99%